Bifidobacterium animalis BD400 protects from collagen-induced arthritis through histidine metabolism - Yang, Yang; Hong, Qing; Zhang, Xuehong; Liu, Zhenmin (Frontiers in Immunology, 2025)
BackgroundRheumatoid arthritis (RA) is a common chronic and systemic autoimmune disease. Numerous clinical studies have indicated a correlation between alterations in gut microbiota and the onset and progression of RA. This research aims to restore intestinal microbiota to a healthy state through the oral administration of Bifidobacterium in the early stages with the goal of delaying the onset and progression of RA.MethodsCollagen-induced arthritis (CIA) rat model was constructed to assess the development of RA using arthritis clinical scores, paw thickness, pathological analysis of knee joint. The immune response was evaluated by determinating specific antibodies and cytokines in serum and synovial fluid. The expression of intestinal barrier protein was analyzed by qPCR to evaluate the intestinal barrier function. Alterations in gut microbiota and metabolites were assessed by 16S rDNA and non-targeted metabolomics.ResultsThe findings reveal that administering Bifidobacterium animalis BD400 orally led to a significant reduction in arthritis clinical scores and paw swelling thickness in CIA rats. Additionally, there was a decrease in osteo-facial fusion and calcified cartilage thickening in the knee joint. Furthermore, the oral administration of B. animalis BD400 resulted in the down-regulation of inflammatory factors TNF-α and collagenase MMP-13 in the knee joint. Levels of specific antibodies (anti-CII IgG, anti-CII IgG1, and anti-CII IgG2a) and cytokine IL-17A in serum, as well as cytokines (TNF-α and IL-1β) in the synovial fluid of B. animalis BD400-treated CIA rats, were significantly reduced (p < 0.05). The gene expression levels of intestinal barrier proteins (occludin-1, MUC-2, and ZO-1) showed a significant increase (p < 0.05) in B. animalis BD400-treated CIA rats. The oral administration of B. animalis BD400 altered the composition of intestinal microorganisms in CIA rats at the phylum and genus levels, particularly affecting the genus HT002. B. animalis BD400 alleviates RA by down-regulating 1-methyl-L-histidine and urocanate in the histidine metabolism, laying a foundation for the RA prevention.ConclusionBy affecting genus HT002 and histidine metabolism in the gut microbiota of CIA rats, B. animalis BD400 restored intestinal permeability, inhibited systemic inflammatory response, and ultimately slowed down the development of RA.